PENGARUH ONLINE CUSTOMER REVIEW, DISKON DAN TAGLINE “GRATIS ONGKIR” TERHADAP KEPUTUSAN PEMBELIAN PADA MARKETPLACE SHOPEE (STUDI KASUS PADA PENGGUNA AKTIF APLIKASI SHOPEE DI DENPASAR) - Benedictus Rezy Winoto Nugroho; Ni Putu Nita Anggraini; I Wayan Gede Antok Setiawan Jodi (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2024)
Today's increasingly rapid developments are directing all aspects of human life towards modernization. Aspects of fulfilling life's needs, such as shopping, of course also lead to modernization and are increasing very rapidly. Marketplace is one of the shopping innovations in this era of modernization. The innovation offered by the marketplace is its role as a third party who becomes an intermediary or gathering place between many sellers and their buyers. Currently, many marketplaces have filled the online shopping market in Indonesia. Shopee, as one of the marketplaces that fills the Indonesian market, has the status of being the youngest player and also the most popular compared to other competing marketplaces such as Tokopedia and Bukalapak, each of which has previously provided e-marketplace services in Indonesia. Therefore, this research aims to uncover the basis of this phenomenon through analyzing the influence of online customer reviews, discounts, and the tagline